Consumer Behavior An economical and marketing overview between the actual American and Czech consumer - Lopez Ramos, Jorge Andres (2010)
The main purpose of this Diploma Thesis is to provide an overview of the Czech Consumer behavior and the American Consumer behavior based on the marketing parameters, economic elements and sociocultural dimensions that affect their purchase decisions. This thesis portraits the different purchase directions and preferences of the modern societies in USA and Czech Republic and the reasoning behind them therefore it will allow future investors and entrepreneurs to understand their business surroundings and make informed decisions towards specific objectives and targets in the both countries.